Transitioning to Gender Equality - Binswanger, Christa; Zimmermann, Andrea (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Gender Equality, the fifth UN Sustainable Development Goal (SDG 5), aims for the elimination of all forms of discrimination against women and girls. It thereby addresses all forms of violence, unpaid and unacknowledged care and domestic work, as well as the need for equal opportunities for leadership at all levels of decision-making in political, economic and public life. Thus, the areas in which changes with regard to gender equality on a global scale are needed are very broad. In this volume, we focus on three main areas of inquiry, 'Sexuality', 'Politics of Difference' and 'Care, Work and Family', and raise the following transversal questions: How can gender be addressed in an intersectional perspective, linking gender to further categories of difference, which are involved in discrimination? In which ways are binary notions of gender taking part in inequality regimes and by which means can these binaries be questioned? How can we measure, control and portray progress with regard to gender equality and how do we, in doing so, define gender? Which multi-, inter- or transdisciplinary perspectives are needed for understanding the diversity of gender, in order to support a transition to 'gender equality'? Transitioning to Gender Equality is part of MDPI's new Open Access book series Transitioning to Sustainability. With this series, MDPI pursues environmentally and socially relevant research which contributes to efforts toward a sustainable world. Transitioning to Sustainability aims to add to the conversation about regional and global sustainable development according to the 17 SDGs. Set to be published in 2020/2021, the book series is intended to reach beyond disciplinary, even academic boundaries. MDPI supports the United Nations Sustainable Development Goals. For use of the SDG logos and design, please see the according Guidelines for the use of the SDG logo, color wheel, and 17 icons.